Isochronous and isothermal annealing of defects - Saliy, Ya.P. (Physics and Chemistry of Solid State, 2024)
The regularities of isothermal and isochronous discrete and continuous annealed material at a constant rate are considered on the example of monomolecular reaction and bimolecular recombination of Frenkel pairs. For isochronous annealing of radiation defects after neutron irradiation of GaP, process parameters were obtained.